Beginning jQuery (eLearning) - Hussain, Frahaan (Packt Publishing, 2018)
"Simple syntax and open coding standards enable developers to deploy applications in a short time. With this course, you will be able to effectively leverage all new features of jQuery 3.0 in your applications. The course begins with teaching the difference between JavaScript and jQuery. You'll learn how to use jQuery with developer tools that are available in all modern browsers. You'll then learn all about selecting elements, handling events, manipulating the document object model, jQuery plugins, advanced Ajax, and several advanced concepts. By the end of the course, you will successfully create a fully featured and efficient single page web application."--Resource description page